“Just Fabric”: The Becoming Black of the (Post)Human in Kazuo Ishiguro’s Klara and the Sun (2021) - Agnibha Banerjee (Sillages Critiques)
In Kazuo Ishiguro’s Klara and the Sun (2021), Klara is an AF (Artificial Friend), one among a range of humanoid automatons manufactured with the objective of keeping affluent, genetically augmented teenagers company. As this essay argues, a disturbing historical parallel to the position of the AFs in the social hierarchy is that of slaves. Like the deployment of black bodies as dehumanized raw materials in plantation economies, the exploitation of the androids in Ishiguro’s novel is premised, I contend, on their exclusion from the category of the “human.” The ethics of such a network of production, consumption, and disposal are hardly ever called into question in the dystopian world of the novel. This essay locates the novel in a flux of debates around the nexus between capitalism, race, artificial intelligence, genetic engineering, and environmental change. It deploys Achille Mbembe’s concept of “the becoming black of the world” to investigate the construction of “posthuman” races through technological advances in Ishiguro’s technologized world. Drawing on Mbembe and other theorists, I demonstrate how the historical objectification and exploitation of black bodies expand to encompass the entire planet, with androids, genetically modified humans, and the earth itself functioning as sites of mining and extraction.